Hubungan Durasi Penggunaan Media Sosial Terhadap Kejadian Asthenopia Pada Mahasiswa FKP UNRI - Agnesi, Olivia Mayola (Universitas Aufa Royhan, 2022)
Introduction: The duration of using gadgets to access social media is unlimited and continuously causes the eyes to see objects on the screen. The eyes are continuously accommodated to see letters or numbers on the monitor which will result in eye fatigue (Asthenopia), research objectives: to determine the relationship between the duration of social media use and the incidence of Asthenopia in students of the Faculty of Nursing, University of Riau, materials and methods: This study using a correlational analytic design with a cross sectional approach. The study was conducted at the Faculty of Nursing, University of Riau with 237 students as samples taken by proportionate stratified random sampling technique by taking into account the inclusion and exclusion criteria. The measuring instrument used is a questionnaire. The analysis used was univariate and bivariate analysis using the Chi Square, the results of the study: The results of the bivariate statistical test showed that there was a relationship between the duration of social media use and the incidence of Asthenopia in students of the Faculty of Nursing, University of Riau with p Value (0.021) < (0.05). Overall, there were 176 people (74.2%) who experienced asthenopia. On average, students experience Asthenopia in the low fatigue category due to the duration of using social media which is not good for eye health, suggestions: Students are expected to be able to control and reduce the duration of social media use in order to prevent the occurrence of Asthenopia.